Building Accident Causes at a Stage of Construction and Acceptance in Operation - Pichugin, Sergiy; Dmytrenko, Lina (International Journal of Engineering and Technology, 2018)
This work covers the consequences of accidents in buildings and structures during the process of construction and acceptance in operation. Attention is focused on the frequency of repetition of this type of accidents, using the graph of the structures’ operation stages. The article describes and analyzes such incidents related to construction. Information on accidents was collected using various sources of information: Internet resources, literary sources, scientific works, as well as reports from the world's journalistic services. The findings are presented more than the past ten years and cover construction incidents around the world. The material is systematized and presented in the form of a table on the basis of which the corresponding diagrams are constructed. The result of the study is the relevant conclusions about the typification of accidents during construction and their regularities. The most common causes of accidents are identified, which allow to obtain more detailed study of the problem and further provide for cases of such accidents at the construction site. Attention is focused on the dependence of the construction’s quality at the level of the country's welfare. In addition, the conclusions contain the main tasks for the solution of this problem and ways of their implementation.
Keywords: buildings and structures; building construction; failure; building accident; destruction of structures